Los Sistemas Promediales. Una Articulación Conceptual Entre La Matemática Y La Física - Carlos Rondero-Guerrero; Arturo Crillo-Pérez; Roberto Noriega-Papaqui (European Scientific Journal, ESJ, 2017)
In this paper we present an alternative analysis of some physical systems through averages. The average systems are defined, which are a clear example of the conceptual articulation between mathematics and physics, which is required to be explicit to foster their learning.